2016
DOI: 10.1002/14651858.cd011325.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Non-pharmacological interventions for cognitive impairment due to systemic cancer treatment

Abstract: Overall, the, albeit low-quality evidence may be interpreted to suggest that non-pharmacological interventions may have the potential to reduce the risk of, or ameliorate, cognitive impairment following systemic cancer treatment. Larger, multi-site studies including an appropriate, active attentional control group, as well as consideration of functional outcomes (e.g. activities of daily living) are required in order to come to firmer conclusions about the benefits or otherwise of this intervention approach. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 124 publications
1
51
0
Order By: Relevance
“…Pharmacotherapies modestly alleviate cognitive deficits [ 73 , 74 ]; however, possible side effects and interactions highlight a need to explore modifiable lifestyle factors. While cognitive behavioral training and physical activity convey functional improvements in cancer survivors [ 75 , 76 ], there are no published dietary strategies. Nevertheless, survivors seek dietary changes to improve symptoms and reduce cancer risk [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacotherapies modestly alleviate cognitive deficits [ 73 , 74 ]; however, possible side effects and interactions highlight a need to explore modifiable lifestyle factors. While cognitive behavioral training and physical activity convey functional improvements in cancer survivors [ 75 , 76 ], there are no published dietary strategies. Nevertheless, survivors seek dietary changes to improve symptoms and reduce cancer risk [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“… 30 In particular, a recent Cochrane review indicated that cognitive training may be effective in improving patients' cognitive function, as well as their QOL. 31 Additionally, behavioural intervention strategies (increasing physical activity levels and fostering supportive social relationships) could be helpful in improving cognitive function among cancer survivors. 12 …”
Section: Discussionmentioning
confidence: 99%
“…So far, only a limited number of potential interventions targeting cancer-related cognitive impairment have been studied [13]. The most promising interventions so far appear to be cognitive training and physical activity [13,14]. However, due to a lack of active control groups and the consideration of biological outcomes, it remains unclear to what extent these interventions are effective.…”
Section: Introductionmentioning
confidence: 99%